Two-component hot-pressing adhesive as well as preparation method and application thereof

By adding vapor-phase silica to the hot-pressing glue and using an organic tin catalyst, the performance of polyether polyol is optimized, and the problem that the bond strength and hot-pressing time of the existing hot-pressing glue on substrates of different materials is difficult to meet at the same time, achieving efficient bonding and breaking effects, which is suitable for the application of fire-proof doors.

CN119639412APending Publication Date: 2025-03-18SHANGHAI JINQIANG ADHESIVE

Patent Information

Application Number
CN202411852750.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing hot pressing glues are difficult to meet the bonding strength and hot pressing time requirements of substrates of different materials at the same time, especially in the application of fireproof doors.

Method used

Two-component hot-pressed glue is synthesized by adding vapor-phase silica (0.1-0.4 wt%) to the hot-pressed glue and using an organic tin catalyst (such as stannous ricinolate catalyst) to optimize the hydroxyl value and viscosity of the polyether polyol.

Benefits of technology

It improves the bonding performance and breaking effect between metal sheets and porous cement boards and paper honeycombs, shortens the hot pressing time, and improves the tensile shear strength to meet the bonding needs of fireproof doors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119639412A_ABST
    Figure CN119639412A_ABST
Patent Text Reader

Abstract

The invention relates to a two-component hot-pressing adhesive as well as a preparation method and application thereof. Comprising a component A and a component B. The component A comprises the following components in parts by weight: 150 parts of castor oil, 50-120 parts of polyether polyol, 150-300 parts of calcium carbonate, 0.5-5 parts of fumed silica, 0.5-5 parts of a surfactant, 0.01-0.5 part of a catalyst and 10-30 parts of an auxiliary agent, and the addition amount of the fumed silica in the hot-pressing adhesive is 0.1-0.4 wt%; and the component B comprises an isocyanate curing agent. The addition amount of the fumed silica in the hot-pressing adhesive is 0.1-0.4 wt%, so that the bonding performance between a metal plate and a porous cement plate and between the metal plate and a paper honeycomb can be improved, and the bonding requirement of a fireproof door is met; the organic tin catalyst is a stannous ricinoleate catalyst, the hot pressing time can be shortened to be within 6 min, and meanwhile the tensile shear strength can be improved to 4 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and more specifically to a two-component hot pressing adhesive and a preparation method and application thereof. Background Art

[0002] Hot-press adhesive is a type of adhesive that softens by heating, is applied to the bonded object, and solidifies under high temperature and high pressure to form an adhesive. Its principle is mainly to use the principle of hot-pressing curing and molding to melt the polymer material and impregnate it on the surface of the fiber or other materials, and achieve a close bond between the materials through high temperature and high pressure. With the continuous improvement of the performance requirements of hot-press adhesives, especially for the bonding of different material substrates, existing hot-press adhesives are difficult to meet the requirements of bonding strength and hot-pressing time at the same time.

[0003] Chinese invention patent CN104232004A discloses a polyurethane heat-sensitive adhesive composition and its preparation method and application. The polyurethane heat-sensitive adhesive composition comprises a polyurethane main agent adhesive and an additive composition, wherein the polyurethane main agent adhesive is a prepolymer with -NCO groups formed by polycondensation of diisocyanate and polyester diol and / or polyether diol, and then a high molecular weight polyurethane main agent adhesive with -OH group termination is obtained by chain extension and crosslinking, the polyurethane main agent adhesive is mixed with a curing agent and a catalyst, and a polyurethane heat-sensitive adhesive composition composed of a small amount of ultraviolet absorber, antioxidant and surfactant is added, stirred evenly, filtered and degassed, and coated to form a film, and the adhesive film prepared by the polyurethane heat-sensitive adhesive composition has the advantages of high transparency, excellent self-absorption, low adhesion, easy peeling and repeated pasting, no residual adhesive, and low price compared with silicone products, but is only suitable for bonding of LCD screens and screen protectors, which limits the scope of application. Summary of the invention

[0004] A first aspect of the present invention provides a two-component hot-pressing adhesive, comprising a component A and a component B, wherein the component A comprises, by weight: 150 parts of castor oil, 50-120 parts of polyether polyol, 150-300 parts of calcium carbonate, 0.5-5 parts of fumed silica, 0.5-5 parts of a surfactant, 0.01-0.5 parts of a catalyst, and 10-30 parts of an additive, wherein the amount of the fumed silica added to the hot-pressing adhesive is 0.1-0.4wt%; and the component B comprises an isocyanate curing agent.

[0005] The research of this application found that the addition of fumed silica in the hot pressing adhesive at a level of 0.1-0.4wt% can improve the bonding performance between metal sheets and porous cement boards and paper honeycombs, meeting the bonding requirements of fire doors. It is possible that the high surface activity and hydrogen bonding of fumed silica during the curing process improve the compatibility with the resin matrix and calcium carbonate, while a specific proportion of fumed silica effectively fills the free volume between polymer segments.

[0006] The isocyanate curing agent includes at least one of diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4′-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, norbornane diisocyanate, cyclohexane dimethylene diisocyanate, phenylmethylene diisocyanate, toluene-2,4-diisocyanate and polydiphenylmethane diisocyanate.

[0007] Preferably, the diisocyanate curing agent includes diphenylmethane diisocyanate.

[0008] Preferably, the amount of the fumed silica added to the hot pressing adhesive is 0.1-0.3wt%.

[0009] The catalyst includes an organotin catalyst.

[0010] Preferably, the organotin catalyst includes at least one of stannous octoate, stannous chloride, butyl tins, and stannous ricinoleates; the butyl tins include butyl stannoic acid, tetrabutyl tin, and dibutyl tin dilaurate.

[0011] Further preferably, the organotin catalyst includes stannous ricinoleate catalyst, and preferred models include: Evonik Chemical KOSMOS EF.

[0012] The present application has found that the use of organotin catalysts can shorten the hot pressing time to less than 8 minutes, and the tensile shear strength can be increased to 3.5MPa. It may be that while promoting the formation of coordination bonds between isocyanates or forming intermediates with polyamines, the interlayer curing rate is stabilized to accelerate the reaction process between amino groups and isocyanates. The present applicant has further found that the organotin catalyst selects stannous ricinoleate catalysts, which can shorten the hot pressing time to less than 6 minutes, and the tensile shear strength can be increased to 4MPa. It may be that ricinoleic acid in stannous ricinoleate catalysts is similarly soluble in castor oil, which improves the dispersion in the system, while blocking the occurrence of side reactions during the hot pressing process, and improving the polymer segment length and segment uniformity of the hot pressing adhesive.

[0013] The surfactant includes a nonionic surfactant.

[0014] Preferably, the surfactant comprises polyethylene glycol having a number average molecular weight of 3000-8000.

[0015] Further preferably, the surfactant comprises polyethylene glycol having a number average molecular weight of 4000-6000.

[0016] The weight ratio of the surfactant to the fumed silica is 1:(0.5-2).

[0017] Preferably, the weight ratio of the surfactant to the fumed silica is 1:(0.8-2).

[0018] Further preferably, the weight ratio of the surfactant to the fumed silica is 1:(0.8-1.2).

[0019] The polyether polyol has a hydroxyl value of 80-250 mgKOH / g and a viscosity of 90-300 mPa·s at 25°C.

[0020] Generally speaking, the higher the hydroxyl value, the more hydroxyl content in the polyether molecule, the higher the reaction activity, and the more cross-linked structures can be formed, thereby improving the bonding strength of the polyurethane material. However, at the same time, the miscibility of polyether polyols with too high hydroxyl values ​​with other components such as isocyanates may deteriorate, which may cause uneven mixing of polyether polyols and isocyanates during the synthesis of polyurethane, thereby affecting the performance of polyurethane materials. At the same time, the applicant found in the experimental process that too high tensile shear strength will affect the breaking effect of fire doors, which may be the difference between the wettability of polymers to different substrates during the curing process. The applicant further found that the hydroxyl value of polyether polyols is 80-250 mgKOH / g, the viscosity is 90-300 mPa·s at 25°C, and the tensile shear strength can be increased to 4.2 MPa, while improving the breaking effect between metal sheets and porous cement boards and paper honeycombs, which may be to improve the wettability of metal substrates and paper substrates during the curing process, and stabilize the curing rate.

[0021] Preferably, the polyether polyol has a hydroxyl value of 80-200 mgKOH / g and a viscosity of 90-250 mPa·s at 25°C.

[0022] More preferably, the polyether polyol has a hydroxyl value of 80-150 mgKOH / g and a viscosity of 100-250 mPa·s at 25°C.

[0023] The particle size of the calcium carbonate is 700-900 meshes.

[0024] As an example, the particle size of the calcium carbonate may be 700 mesh, 750 mesh, 800 mesh, 850 mesh or 900 mesh.

[0025] The calcium carbonate includes at least one of light calcium carbonate, heavy calcium carbonate and activated calcium carbonate.

[0026] Preferably, the calcium carbonate includes heavy calcium carbonate and activated calcium carbonate, and the weight ratio of the heavy calcium carbonate to the activated calcium carbonate is (18-25):1.

[0027] Further preferably, the weight ratio of the heavy calcium carbonate to the activated calcium carbonate is 20:1.

[0028] The auxiliary agent includes a plasticizer and / or a defoamer.

[0029] The plasticizer includes at least one of dibutyl phthalate, dioctyl phthalate, diene terephthalate, and epoxy triglyceride.

[0030] Preferably, the plasticizer comprises dibutyl phthalate.

[0031] The defoaming agent includes an organosilicon defoaming agent.

[0032] Preferably, the organosilicon defoaming agent includes at least one of trimethyl silicone oil, dimethyl polysiloxane, silicone paste and polysiloxane.

[0033] Further preferably, the organosilicon defoamer comprises polysiloxane.

[0034] A second aspect of the present invention provides a method for preparing a two-component hot-pressed adhesive, comprising the following steps: S1, mixing castor oil, polyether polyol and fumed silica and stirring uniformly; S2, add calcium carbonate and dispersant, vacuum and stir evenly; S3, adding an auxiliary agent and a catalyst and stirring evenly to obtain component A; S4, prepare component B.

[0035] A third aspect of the present invention provides an application of a two-component hot-pressed adhesive for use in the preparation of fire doors.

[0036] Preferably, it is used for bonding the core material and the plate material of a fire door.

[0037] Further preferably, the core material comprises a porous cement board or a paper honeycomb, and the plate material comprises a metal, and preferably the plate material is a color-coated steel plate.

[0038] Beneficial Effects 1. The addition amount of fumed silica in hot pressing adhesive is 0.1-0.4wt%, which can improve the bonding performance between metal sheet and porous cement board and paper honeycomb, and meet the bonding requirements of fire doors.

[0039] 2. The use of organic tin catalysts can shorten the hot pressing time to less than 8 minutes, and the tensile shear strength can be increased to 3.5MPa.

[0040] 3. Organic tin catalysts: Selecting stannous ricinoleate catalysts can shorten the hot pressing time to less than 6 minutes, and at the same time the tensile shear strength can be increased to 4 MPa.

[0041] 4. The hydroxyl value of the polyether polyol is 80-250 mgKOH / g, the viscosity is 90-300 mPa·s at 25°C, the tensile shear strength can be increased to 4.2 MPa, and the breaking effect between metal plates and porous cement boards and paper honeycombs can be improved.

[0042] 5. Adding non-ionic surfactants, especially polyethylene glycol with a number average molecular weight of 3000-8000, can further improve the construction performance of hot pressing adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is the material breaking effect of the glue prepared according to the formula of Example 1 (the core material is porous cement board).

[0044] Figure 2 This is the material breaking effect of the glue prepared according to the formula of Example 1 (the core material is paper honeycomb).

[0045] Figure 3 This is the material breaking effect of the glue prepared by the formula of Comparative Example 1 (the core material is porous cement board).

[0046] Figure 4 This is the material breaking effect of the glue prepared by the formula of Comparative Example 1 (the core material is paper honeycomb).

[0047] Figure 5 This is the material breaking effect of the glue prepared by the formula of Comparative Example 2 (the core material is porous cement board).

[0048] Figure 6 This is the material breaking effect of the glue prepared by the formula of Comparative Example 2 (the core material is paper honeycomb).

[0049] Figure 7 This is the material breaking effect of the glue prepared by the formula of comparative example 3 (the core material is porous cement board).

[0050] Figure 8 This is the material breaking effect of the glue prepared by the formula of Comparative Example 3 (the core material is paper honeycomb).

[0051] Fig. 9 This is the material breaking effect of the glue prepared by the formula of Comparative Example 4 (the core material is porous cement board).

[0052] Fig.10 This is the material breaking effect of the glue prepared by the formula of Comparative Example 4 (the core material is paper honeycomb).

[0053] Fig.11 This is the material breaking effect of the glue prepared by the formula of comparative example 5 (the core material is porous cement board).

[0054] Fig.12 This is the material breaking effect of the glue prepared by the formula of Comparative Example 5 (the core material is paper honeycomb).

[0055] Fig.13 This is the material breaking effect of the glue prepared by the formula of comparative example 6 (the core material is porous cement board).

[0056] Fig.14 This is the material breaking effect of the glue prepared by the formula of Comparative Example 6 (the core material is paper honeycomb).

[0057] Fig.15 This is the material breaking effect of the glue prepared by the formula of Comparative Example 7 (the core material is porous cement board).

[0058] Fig.16 This is the material breaking effect of the glue prepared by the formula of Comparative Example 7 (the core material is paper honeycomb).

[0059] Fig.17 This is the material breaking effect of the glue prepared according to the formula of Example 2 (the core material is porous cement board).

[0060] Fig.18 This is the material breaking effect of the glue prepared according to the formula of Example 2 (the core material is paper honeycomb).

[0061] Fig.19 This is the material breaking effect of the glue prepared by the formula of Example 3 (the core material is porous cement board).

[0062] Fig. 20 This is the material breaking effect of the glue prepared according to the formula of Example 3 (the core material is paper honeycomb). DETAILED DESCRIPTION

[0063] Example 1 A two-component hot-pressing adhesive, consisting of component A and component B, wherein component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 220 parts by weight of calcium carbonate, 1 part by weight of fumed silica (Hubei Huifu Nanomaterials Co., Ltd., HL-150), 1 part by weight of surfactant, 0.08 parts by weight of catalyst, and 20.5 parts by weight of additive; component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0064] The catalyst is a stannous ricinoleate catalyst purchased from Evonik Chemicals, model: KOSMOS EF.

[0065] The polyether polyol has a hydroxyl value of 109-115 mgKOH / g and a viscosity of 120-180 mPa·s at 25° C. and is purchased from Tianjin Zhonghe Shengtai Chemical Industry, model: DL-1000D.

[0066] The calcium carbonate includes heavy calcium carbonate (800 mesh, purchased from Helixin) and activated calcium carbonate (800 mesh, purchased from Guangxi Owu Technology Co., Ltd.), and the weight ratio of the heavy calcium carbonate to the activated calcium carbonate is 20:1.

[0067] The auxiliary agent is 20 parts of plasticizer (dibutyl phthalate) and 0.5 parts of defoamer (Xingrui, SGR1832).

[0068] The surfactant is a non-ionic surfactant, polyethylene glycol with a number average molecular weight of 6000, purchased from Nantong Qianhe Chemical, PEG-6000.

[0069] A method for preparing a two-component hot-pressing adhesive comprises the following steps: S1, mix castor oil, polyether polyol and fumed silica and stir for 20 min at a speed of 800 r / min; S2, add calcium carbonate and dispersant, vacuum and stir for 1h, speed 1300r / min; S3, add the additive and catalyst and stir for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0070] Example 2 A two-component hot-pressing adhesive, consisting of component A and component B, wherein component A is calculated by weight as follows: 150 parts of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts of polyether polyol, 300 parts of calcium carbonate, 1 part of fumed silica (Hubei Huifu Nanomaterials Co., Ltd., HL-150), 1 part of surfactant, 0.08 parts of catalyst, and 20.5 parts of additive; component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0071] The catalyst is a stannous ricinoleate catalyst purchased from Evonik Chemicals, model: KOSMOS EF.

[0072] The polyether polyol has a hydroxyl value of 109-115 mgKOH / g and a viscosity of 120-180 mPa·s at 25° C. and is purchased from Tianjin Zhonghe Shengtai Chemical Industry, model: DL-1000D.

[0073] The calcium carbonate includes heavy calcium carbonate (800 mesh, purchased from Helixin) and activated calcium carbonate (800 mesh, purchased from Guangxi Owu Technology Co., Ltd.), and the weight ratio of the heavy calcium carbonate to the activated calcium carbonate is 29:1.

[0074] The auxiliary agent is 20 parts of plasticizer (dibutyl phthalate) and 0.5 parts of defoamer (Xingrui, SGR1832).

[0075] The surfactant is a non-ionic surfactant, polyethylene glycol with a number average molecular weight of 6000, purchased from Nantong Qianhe Chemical, PEG-6000.

[0076] A method for preparing a two-component hot-pressing adhesive comprises the following steps: S1, mix castor oil, polyether polyol and fumed silica and stir for 20 min at a speed of 800 r / min; S2, add calcium carbonate and dispersant, vacuum and stir for 1h, speed 1300r / min; S3, add the additive and catalyst and stir for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0077] Example 3 A two-component hot-pressing adhesive, consisting of component A and component B, wherein component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 50 parts by weight of polyether polyol, 160 parts by weight of calcium carbonate, 1 part by weight of fumed silica (Hubei Huifu Nanomaterials Co., Ltd., HL-150), 0.5 parts by weight of surfactant, 0.08 parts by weight of catalyst, and 10.5 parts by weight of additive; component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0078] The catalyst is a stannous ricinoleate catalyst purchased from Evonik Chemicals, model: KOSMOS EF.

[0079] The polyether polyol has a hydroxyl value of 109-115 mgKOH / g and a viscosity of 120-180 mPa·s at 25° C. and is purchased from Tianjin Zhonghe Shengtai Chemical Industry, model: DL-1000D.

[0080] The calcium carbonate includes heavy calcium carbonate (800 mesh, purchased from Helixin) and activated calcium carbonate (800 mesh, purchased from Guangxi Owu Technology Co., Ltd.), and the weight ratio of the heavy calcium carbonate to the activated calcium carbonate is 15:1.

[0081] The auxiliary agent is 10 parts of plasticizer (dibutyl phthalate) and 0.5 parts of defoamer (Xingrui, SGR1832).

[0082] The surfactant is a non-ionic surfactant, polyethylene glycol with a number average molecular weight of 6000, purchased from Nantong Qianhe Chemical, PEG-6000.

[0083] A method for preparing a two-component hot-pressing adhesive comprises the following steps: S1, mix castor oil, polyether polyol and fumed silica and stir for 20 min at a speed of 800 r / min; S2, add calcium carbonate and dispersant, vacuum and stir for 1h, speed 1300r / min; S3, add the additive and catalyst and stir for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0084] Comparative Example 1 A two-component hot-pressing adhesive, consisting of component A and component B, wherein component A is calculated by weight as follows: 150 parts of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts of polyether polyol, 220 parts of calcium carbonate, 1 part of fumed silica (Hubei Huifu Nanomaterials Co., Ltd., HL-150), 1 part of surfactant (Nantong Qianhe Chemical, PEG-6000), 0.08 parts of catalyst, and 20.5 parts of additives; component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0085] The catalyst was purchased from Evonik Chemicals, model: KOSMOS EF.

[0086] The polyether polyol was purchased from Tianjin Zhonghe Shengtai Chemical Industry, model: DL-400.

[0087] The calcium carbonate includes heavy calcium carbonate (800 mesh, purchased from Helixin) and activated calcium carbonate (800 mesh, purchased from Guangxi Owu Technology Co., Ltd.), and the weight ratio of the heavy calcium carbonate to the activated calcium carbonate is 20:1.

[0088] The auxiliary agent is 20 parts of plasticizer (dibutyl phthalate) and 0.5 parts of defoamer (Xingrui, SGR1832).

[0089] A method for preparing a two-component hot-pressing adhesive comprises the following steps: S1, mix castor oil, polyether polyol and fumed silica and stir for 20 min at a speed of 800 r / min; S2, add calcium carbonate and dispersant, vacuum and stir for 1h, speed 1300r / min; S3, add the additive and catalyst and stir for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0090] Comparative Example 2 A two-component hot-pressing adhesive, consisting of component A and component B, wherein component A is calculated by weight as follows: 150 parts of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts of polyether polyol, 220 parts of calcium carbonate, 1 part of fumed silica (Hubei Huifu Nanomaterials Co., Ltd., HL-150), 1 part of surfactant (Nantong Qianhe Chemical, PEG-6000), 0.08 parts of catalyst, and 20.5 parts of additives; component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0091] The catalyst was purchased from Evonik Chemicals, model: KOSMOS EF.

[0092] The polyether polyol was purchased from Tianjin Zhonghe Shengtai Chemical Industry, model: EP-330N (G).

[0093] The calcium carbonate includes heavy calcium carbonate (800 mesh, purchased from Helixin) and activated calcium carbonate (800 mesh, purchased from Guangxi Owu Technology Co., Ltd.), and the weight ratio of the heavy calcium carbonate to the activated calcium carbonate is 20:1.

[0094] The auxiliary agent is 20 parts of plasticizer (dibutyl phthalate) and 0.5 parts of defoamer (Xingrui, SGR1832).

[0095] A method for preparing a two-component hot-pressing adhesive comprises the following steps: S1, mix castor oil, polyether polyol and fumed silica and stir for 20 min at a speed of 800 r / min; S2, add calcium carbonate and dispersant, vacuum and stir for 1h, speed 1300r / min; S3, add the additive and catalyst and stir for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0096] Comparative Example 3 A two-component hot-pressing adhesive, consisting of component A and component B, wherein component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 220 parts by weight of calcium carbonate, 1 part by weight of silica (Shandong Kasong New Materials Co., Ltd., 300-mesh silica prepared by precipitation method), 1 part by weight of surfactant (Nantong Qianhe Chemical, PEG-6000), 0.08 parts by weight of catalyst, and 20.5 parts by weight of additive; component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0097] The catalyst was purchased from Evonik Chemicals, model: KOSMOS EF.

[0098] The polyether polyol was purchased from Tianjin Zhonghe Shengtai Chemical Industry, model: DL-1000D.

[0099] The calcium carbonate includes heavy calcium carbonate (800 mesh, purchased from Helixin) and activated calcium carbonate (800 mesh, purchased from Guangxi Owu Technology Co., Ltd.), and the weight ratio of the heavy calcium carbonate to the activated calcium carbonate is 20:1.

[0100] The auxiliary agent is 20 parts of plasticizer (dibutyl phthalate) and 0.5 parts of defoamer (Xingrui, SGR1832).

[0101] A method for preparing a two-component hot-pressing adhesive comprises the following steps: S1, mix castor oil, polyether polyol and fumed silica and stir for 20 min at a speed of 800 r / min; S2, add calcium carbonate and dispersant, vacuum and stir for 1h, speed 1300r / min; S3, add the additive and catalyst and stir for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0102] Comparative Example 4 A two-component hot-pressing adhesive, consisting of component A and component B, wherein component A is calculated by weight as follows: 150 parts of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts of polyether polyol, 220 parts of calcium carbonate, 1 part of fumed silica (Hubei Huifu Nanomaterials Co., Ltd., HL-150), 1 part of surfactant (Nantong Qianhe Chemical, PEG-6000), 0.08 parts of catalyst, and 20.5 parts of additives; component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0103] The catalyst is dibutyltin dilaurate.

[0104] The polyether polyol was purchased from Tianjin Zhonghe Shengtai Chemical Industry, model: DL-1000D.

[0105] The calcium carbonate includes heavy calcium carbonate (800 mesh, purchased from Helixin) and activated calcium carbonate (800 mesh, purchased from Guangxi Owu Technology Co., Ltd.), and the weight ratio of the heavy calcium carbonate to the activated calcium carbonate is 20:1.

[0106] The auxiliary agent is 20 parts of plasticizer (dibutyl phthalate) and 0.5 parts of defoamer (Xingrui, SGR1832).

[0107] A method for preparing a two-component hot-pressing adhesive comprises the following steps: S1, mix castor oil, polyether polyol and fumed silica and stir for 20 min at a speed of 800 r / min; S2, add calcium carbonate and dispersant, vacuum and stir for 1h, speed 1300r / min; S3, add the additive and catalyst and stir for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0108] Comparative Example 5 A two-component hot-pressing adhesive, consisting of component A and component B, wherein component A is calculated by weight as follows: 150 parts of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts of polyether polyol, 220 parts of calcium carbonate, 1 part of fumed silica (Hubei Huifu Nanomaterials Co., Ltd., HL-150), 1 part of surfactant (Nantong Qianhe Chemical, PEG-6000), 0.08 parts of catalyst, and 20.5 parts of additives; component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0109] The catalyst is an organic titanium catalyst, brand: Dofukate, model: Unilink 2200.

[0110] The polyether polyol was purchased from Tianjin Zhonghe Shengtai Chemical Industry, model: DL-1000D.

[0111] The calcium carbonate includes heavy calcium carbonate (800 mesh, purchased from Helixin) and activated calcium carbonate (800 mesh, purchased from Guangxi Owu Technology Co., Ltd.), and the weight ratio of the heavy calcium carbonate to the activated calcium carbonate is 20:1.

[0112] The auxiliary agent is 20 parts of plasticizer (dibutyl phthalate) and 0.5 parts of defoamer (Xingrui, SGR1832).

[0113] A method for preparing a two-component hot-pressing adhesive comprises the following steps: S1, mix castor oil, polyether polyol and fumed silica and stir for 20 min at a speed of 800 r / min; S2, add calcium carbonate and dispersant, vacuum and stir for 1h, speed 1300r / min; S3, add the additive and catalyst and stir for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0114] Comparative Example 6 A two-component hot-pressing adhesive, consisting of component A and component B, wherein component A is calculated by weight as follows: 150 parts of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts of polyether polyol, 220 parts of calcium carbonate, 0.3 parts of fumed silica (Hubei Huifu Nanomaterials Co., Ltd., HL-150), 1 part of surfactant (Nantong Qianhe Chemical, PEG-6000), 0.08 parts of catalyst, and 20.5 parts of additives; component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0115] The catalyst was purchased from Evonik Chemicals, model: KOSMOS EF.

[0116] The polyether polyol was purchased from Tianjin Zhonghe Shengtai Chemical Industry, model: DL-1000D.

[0117] The calcium carbonate includes heavy calcium carbonate (800 mesh, purchased from Helixin) and activated calcium carbonate (800 mesh, purchased from Guangxi Owu Technology Co., Ltd.), and the weight ratio of the heavy calcium carbonate to the activated calcium carbonate is 20:1.

[0118] The auxiliary agent is 20 parts of plasticizer (dibutyl phthalate) and 0.5 parts of defoamer (Xingrui, SGR1832).

[0119] A method for preparing a two-component hot-pressing adhesive comprises the following steps: S1, mix castor oil, polyether polyol and fumed silica and stir for 20 min at a speed of 800 r / min; S2, add calcium carbonate and dispersant, vacuum and stir for 1h, speed 1300r / min; S3, add the additive and catalyst and stir for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0120] Comparative Example 7 A two-component hot-pressing adhesive, consisting of component A and component B, wherein component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 220 parts by weight of calcium carbonate, 3 parts by weight of fumed silica (Hubei Huifu Nanomaterials Co., Ltd., HL-150), 1 part by weight of surfactant (Nantong Qianhe Chemical, PEG-6000), 0.08 parts by weight of catalyst, and 20.5 parts by weight of additive; component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0121] The catalyst was purchased from Evonik Chemicals, model: KOSMOS EF.

[0122] The polyether polyol was purchased from Tianjin Zhonghe Shengtai Chemical Industry, model: DL-1000D.

[0123] The calcium carbonate includes heavy calcium carbonate (800 mesh, purchased from Helixin) and activated calcium carbonate (800 mesh, purchased from Guangxi Owu Technology Co., Ltd.), and the weight ratio of the heavy calcium carbonate to the activated calcium carbonate is 20:1.

[0124] The auxiliary agent is 20 parts of plasticizer (dibutyl phthalate) and 0.5 parts of defoamer (Xingrui, SGR1832).

[0125] A method for preparing a two-component hot-pressing adhesive comprises the following steps: S1, mix castor oil, polyether polyol and fumed silica and stir for 20 min at a speed of 800 r / min; S2, add calcium carbonate and dispersant, vacuum and stir for 1h, speed 1300r / min; S3, add the additive and catalyst and stir for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0126] Performance testing methods and data Preparation of glue: Component A and component B in the embodiment and the comparative example were mixed at a weight ratio of 100:20 respectively; the following performance tests were performed on the glue.

[0127] (1) The degree of damage to the core material at the bonding point (damage effect): Use glue (200g of glue per square) to bond the plate, core material, and plate together. The plate is a color steel plate, and the core material is a porous cement board or paper honeycomb. Put it into a hot press at 60°C for 8 minutes. After cooling for 2 hours, tear open one side of the plate to see the degree of damage to the core material at the bonding point. Use "high, medium, and low" to score and evaluate the degree of damage. A high damage rate means a good bonding effect. According to the residual area of ​​the core material on the contact surface, it is divided into "high", "medium" and "low". Specifically: a residual area of ​​not less than 80% is "high", a residual area of ​​50-80% is "medium", and a residual area of ​​less than 50% is "low". Among them, Example 1 and Comparative Example 2 are partially manually sprayed, and the rest are fully scraped. The test results are as follows Figure 1-20 And as shown in Table 1.

[0128] (2) Tensile shear strength: According to the national standard GB / T7124 / 2008, the substrate is a composite of two small aluminum sheets with a length of 10 cm, a width of 2.5 cm, and a thickness of 4 mm (the front area must be polished before use). The test is carried out after curing for 7 days. The test results are recorded in Table 2.

[0129] (3) Hot pressing time: Glue is sprayed on the color steel plate, filled with paper honeycomb, and then covered with a layer of color steel plate sprayed with glue, and sent to the press. After the pressure is released, observe whether the bonding between the color steel plate and the paper honeycomb is cracked, debonded, bounced, or colloid is wired. Record the minimum hot pressing time without the above conditions. The test results are recorded in Table 2.

[0130] Table 1

[0131] Table 2

[0132] Combining Tables 1 and 2 and Figure 1-20 The results show that the shear strength of the two-component hot-pressing adhesive prepared in the present application can reach 4.2MPa, and the hot-pressing time can be controlled within 6min, which has excellent breaking effect when applied to fireproof boards; however, using polyether polyols with too high a hydroxyl value will result in poor bonding performance for fireproof boards with paper honeycomb as the core material; using polyether polyols with too low a hydroxyl value will result in poor shear strength; replacing silica with silica produced by precipitation method will result in poor breaking effect and shear strength when applied to fireproof boards; replacing the catalyst with dibutyltin dilaurate or organic titanium will result in poor breaking effect and shear strength and increase the hot-pressing time; using too much or too little fumed silica will result in poor breaking effect.

Claims

1. A two-component hot pressing adhesive, characterized in that: The invention comprises component A and component B, wherein component A comprises, by weight, 150 parts of castor oil, 50-120 parts of polyether polyol, 150-300 parts of calcium carbonate, 0.5-5 parts of fumed silica, 0.5-5 parts of surfactant, 0.01-0.5 parts of catalyst, and 10-30 parts of auxiliary agent, and the amount of fumed silica added to the hot pressing adhesive is 0.1-0.4wt%; and component B comprises an isocyanate curing agent.

2. The two-component hot pressing adhesive according to claim 1, characterized in that: The catalyst includes an organotin catalyst.

3. The two-component hot pressing adhesive according to claim 2, characterized in that: The organotin catalyst includes stannous ricinoleate catalyst.

4. The two-component hot pressing adhesive according to claim 3, characterized in that: The surfactant includes a nonionic surfactant.

5. The two-component hot pressing adhesive according to claim 1 or 4, characterized in that: The surfactant includes polyethylene glycol with a number average molecular weight of 3000-8000.

6. The two-component hot pressing adhesive according to claim 5, characterized in that: The weight ratio of the surfactant to the fumed silica is 1:(0.5-2).

7. The two-component hot pressing adhesive according to claim 1 or 6, characterized in that: The polyether polyol has a hydroxyl value of 80-250 mgKOH / g and a viscosity of 90-300 mPa·s at 25°C.

8. The two-component hot pressing adhesive according to claim 7, characterized in that: The auxiliary agent includes a plasticizer and / or a defoamer.

9. A method for preparing the two-component hot pressing adhesive according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing castor oil, polyether polyol and fumed silica and stirring uniformly; S2, add calcium carbonate and dispersant, vacuum and stir evenly; S3, adding an auxiliary agent and a catalyst and stirring evenly to obtain component A; S4, prepare component B.

10. An application of the two-component hot pressing adhesive according to claim 1 or 8, characterized in that: Used in the preparation of fire doors.

Citation Information

Patent Citations

  • Polyurethane pressure-sensitive adhesive composition and preparation method and application thereof

    CN104232004A

Cited By

  • Hot-pressing adhesive for full-automatic craft fireproof door and preparation method of hot-pressing adhesive

    CN121652752A